Alternative splicing expands the antiviral IFITM repertoire in Chinese rufous horseshoe bats. - Nelly S C Mak; Jingyan Liu; Dan Zhang; Jordan Taylor; Xiaomeng Li; Kazi Rahman; Feiyu Chen; Siddhartha A K Datta; Kin Kui Lai; Zhengli Shi; Nigel Temperton; Aaron T Irving; et al. (PLoS Pathogens)
Species-specific interferon responses are shaped by the virus-host arms race. The human interferon-induced transmembrane protein (IFITM) family consists of three antiviral IFITM genes that arose by gene duplication. These genes restrict virus entry and are key players in antiviral interferon responses. The unique IFITM repertoires in different species influence their resistance to viral infections, but the role of IFITMs in shaping the enhanced antiviral immunity of reservoir bat species is unclear. Here, we identified an IFITM gene in Chinese rufous horseshoe bat, a natural host of severe acute respiratory syndrome (SARS)-related coronaviruses, that is alternatively spliced to produce two IFITM isoforms in native cells as shown by transcriptomics. These bat IFITMs have conserved structures in vitro as demonstrated by circular dichroism spectroscopy, yet they exhibit distinct antiviral specificities against influenza A virus, Nipah virus and coronaviruses including SARS-CoV, SARS-CoV-2 and MERS-CoV. In parallel with human IFITM1-3, bat IFITM isoforms localize to distinct sites of virus entry which influences their antiviral potency. Further bioinformatic analysis of IFITM repertoires in 206 mammals reveals that alternative splicing is a recurring strategy for IFITM diversification, albeit less widely adopted than gene duplication. These findings demonstrate that alternative splicing is a key strategy for evolutionary diversification in the IFITM family. Our study also highlights an example of convergent evolution where species-specific selection pressures led to expansion of the IFITM family through multiple means, underscoring the importance of IFITM diversity as a component of innate immunity.